Pengaruh Lembar Stimulus Emosi terhadap Kemampuan Menulis Puisi Siswa SMP: The Effect of Emotional Stimulus Sheets on Junior High School Students' Poetry Writing Ability - Indragandi Indragandi; Nurlaelah Mahmud; Suleha Ecca; Jumiati Lanta (Information Technology and Science(ITScience), 2026)
Poetry writing instruction at the junior high school level still tends to be mechanical. It does not accommodate students' exploration of emotions and personal experiences, resulting in low-quality poetic expression. Therefore, learning media are needed that can activate students' affective aspects before the writing process. This study is based on the Stimulus-Organism-Response (SOR) theory, which holds that students' learning responses are influenced by stimuli processed through internal conditions, especially emotions and imagination. This study aims to examine the effect of using emotional stimulus sheets on students' poetry writing abilities. This study used a quantitative, quasi-experimental, one-group pretest–posttest design. The research sample comprised 20 students from class VIII A at Muhammadiyah Rappang Junior High School. Data were collected via a poetry-writing test and analyzed using descriptive statistics, normality tests, and paired t-tests. The results showed that the average score for students' poetry-writing abilities increased from 54.05 in the pretest to 73.45 in the posttest. The results of the paired t-test showed a significance value of 0.000 (< 0.05) and a t-value of -6.228, indicating a significant difference between before and after treatment. The use of emotional stimulus sheets significantly improved students' poetry-writing skills. This media is an effective, affect-based learning tool that can activate students' emotions, imagination, and personal experiences, resulting in more expressive and meaningful poetry.